Biology and engineering of stem cell niches - Vishwakarma, Ajaykumar; Karp, Jeffrey (Elsevier/Academic Press, 2017)
Biology and Engineering of Stem Cell Niches covers a wide spectrum of research and current knowledge on embryonic and adult stem cell niches, focusing on the understanding of stem cell niche molecules and signaling mechanisms, including cell-cell/cell-matrix interactions. The book comprehensively reviews factors regulating stem cell behavior and the corresponding approaches for understanding the subsequent effect of providing the proper matrix molecules, mechanical cues, and/or chemical cues. It encompasses a variety of tools and techniques for developing biomaterials-based methods to model synthetic stem cell niches in vivo, or to enhance and direct stem cell fate in vitro. A final section of the book discusses stem cell niche bioengineering strategies and current advances in each tissue type.--Provided by publisher.